Come in un 'vertep': una lettura di "Bab'e carstvo" di A. Čechov tra narrazione e teatro - Rosanna Casari (eSamizdat)
The study aims to analyse the image and function of the house-space, the role of objects inside the house, and their relation to the inner world of the heroine, Anna Akimovna, in Chekhov’s A Woman’s Kingdom. Anna Akimovna’s house is a typical Russian merchant house divided into two floors: upstairs and downstairs. Her life, too, is divided into two parts: her happy and carefree childhood spent in a popular, peripheral area in Moscow and her current life as the owner of a successful factory with all the responsibilities that entails. Now she lives upstairs, that place where she receives intellectual and particular guests. The downstairs floor, on the contrary, is the place of traditional life; in that place live the old aunt and the old woman cook, there the pilgrim women receive guests. This definite spatial subdivision corresponds to a temporal rhythm found in the division of Christmas, which Anna Akimovna delineates as she anxiously crosses between the upstairs and downstairs spheres throughout the day. Much as the house is divided, so is the day. It is separated into four movements that proceed according to ceremony, which never changes, but Anna desires change and hopes her destiny will be fulfilled through her possible marriage to Pimenov. Although Anna Akimovna seeks an escape from her loneliness, her dream will remain a mirage that cannot be fulfilled neither upstairs nor downstairs because she seems to be condemned to live in a ‘middle territory’ without exit. This story was considered by Robert L. Jackson and Carol A. Flath a four act drama, but, in my opinion, this two level-spatial structure is something else: it reminds us of a traditional vertep (old Russian puppet theatre in Christmas time).